High prevalence of older Australians with one or more joint replacements: estimating the population at risk for late complications of arthroplasty. Issue 5 (2nd March 2020) - Manning, Laurens; Davis, Joshua S.; Robinson, Owen; Clark, Ben; Lorimer, Michelle; de Steiger, Richard; Graves, Stephen E.
Abstract: Background: To provide an estimate of the population at risk for late complications of arthroplasty, we aimed to determine the prevalence of Australians living with one or more joint replacements. Methods: Data included all arthroplasty procedures performed in Australia from 2003 to 2016 recorded by the Australian Orthopaedic Association National Joint Replacement Registry. The age‐ and gender‐specific Australian population was obtained from the Australian Bureau of Statistics and used as denominator data. Survival data for each joint replacement, and of individuals, were used to estimate the arthroplasty prevalence. Analyses by age, gender and joint replacement site were undertaken. Prevalence estimates were augmented with procedural data captured before 2003 modelled with assumptions accounting for age and gender distributions, overall survival and arthroplasty revision rates. Results: By the end of 2016, there were 824 769 Australians living with at least one joint replacement, representing 3.4% of the total population. The prevalence of joint replacement is increasing in all age groups, but was highest amongst older Australians, with an overall prevalence of 22.5%, and 13.3% in those aged >85 years and 65–84 years, respectively. The prevalence of people living with multiple joint replacements is increasing more rapidly than patients who have undergone only one joint replacement procedure. Conclusion: The prevalence of older Australians living with joint replacements is rapidly increasing, providing an estimate of the population‐at‐risk for late complications of arthroplasty including peri‐prosthetic infection and fracture. Abstract : There are almost no international data on the prevalence of arthroplasty in high‐income countries, where these operations are an important component of maintaining musculoskeletal health in older patients. These Australian data link arthroplasty operations with patient‐level data that are linked to the National Death Register and demonstrate that >800 000 Australians are living with at least one joint replacement, including >22% of all Australians aged over 85 years. Furthermore, we show striking increases in the number of Australians living with multiple joint replacements including 25 000 living with three or more joint replacements and 47 with all six large joints replaced.